The whale warriors : on board a pirate ship in the battle to save the world's largest mammals - Heller, Peter, 1959- (Pymble, N.S.W. : HarperCollins Publishers, 2007)
In The Whale Warriors, veteran adventure writer Peter Heller takes us on a hair-raising journey with a vigilante crew on their mission to stop illegal Japanese whaling in the stormy, remote seas off the forbidding shores of Antarctica.
Contents: 1. Storm -- 2. Prelude -- 3. The Farley Mowat -- 4. The Good Captain -- 5. Final Preparations -- 6. Salt -- 7. Lifeboat Drill -- 8. Hobart -- 9. Southern Ocean --10. Ghost -- 11. Ice -- 12. The Whale Spoke to Justin -- 13. Uninvited Guest -- 14. Force 7 -- 15. Force 8 -- 16. The Law of the Sea -- 17. Flight -- 18. The Definition of a Pirate -- 19. Among the Penguins -- 20. A Good Day to Die -- Epilogue.
Originally published: New York : Free Press, 2007.
Farley Mowat was the flagship of the Sea Shepherd Conservation Society.
Keywords: Heller, Peter, -- 1959- -- Travel -- Antarctic Ocean; Heller, Peter, -- 1959- -- Diaries; Farley Mowat (Trawler); Sea Shepherd Conservation Society; Whaling -- Antarctic Ocean; Whales -- Conservation -- Antarctic Ocean